MANAJEMEN ZAKAT DI INDONESIA SEBAGAI PEMBERDAYAAN EKONOMI UMAT - Dita Afrina (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2018)
ABSTRACTThe economic empowerment of the ummah means an effort to improve the dignity of the layers of the Islamic community from the conditions of being unable, and escape from the pitfalls of poverty and economic underdevelopment. In other words, as an effort to build the independence of the people in the economic field, zakat management exists as well-organized activities where there is a process to achieve these goals. Zakat management consists of planning, organizing, implementing, and controlling or supervising carried out to determine and achieve the targets that have been determined through the use of human resources and other resources.Keywords: Zakat Management, Community Economic Empowerment, Planning, Organizing, Implementing, Controlling.ABSTRAKPemberdayaan ekonomi umat merupakan upaya untuk meningkatkan harkat dan martabat lapisan masyarakat Islam dari kondisi tidak mampu, serta melepaskan diri dari perangkap kemiskinan dan keterbelakangan ekonomi. Dengan kata lain, sebagai upaya membangun kemandirian umat di bidang ekonomi, manajemen zakat hadir sebagai suatu kegiatan-kegiatan yang diorganisir dengan baik dimana terdapat proses untuk mencapai tujuan-tujuan tersebut. Manajemen zakat terdiri dari perencanaan, pengorganisasian, pelaksanaan, serta pengendalian atau pengawasan yang dilakukan untuk menentukan serta mencapai sasaran yang telah ditentukan melalui pemanfaatan sumber daya manusia dan sumber daya lainnya.Kata kunci: Manajemen Zakat, Pemberdayaan Ekonomi Umat, Perencanaan, Pengelolaan, Penerapan, Pengendalian.